(untitled) (Communications in Mathematical Research, 2021)
In this note, we prove a concentration theorem of (R, p)-anders. As a simple corollary, one can prove that (X, p)-anders do not admit coarse embeddings into Hadamard manifolds with bounded sectional curvatures.